Infikovaná pseudoaneuryzma a. brachialis--raritní kazuistika u dlouholetého intravenózního narkomana - Biros, E; Maresch, M; Rathous, I; Sváb, J (Rozhledy v chirurgii, 2007)
INTRODUCTION: Intravenous drug abuse brings many infectious and surgical complications. Considering the duration of a drug scene in Czech Republic, pseudoaneurysms are not frequent complications, but we can expect their increased frequency with time. METHODS: A 27-year-old patient with known history of parenteral drug abuse (heroin, pervitin) was treated at our department during the autumn of 2006. He had self-injected heroin into an armpit four days before his appearance in our outpatient department. An abscess of his left arm and armpit resulting from cellulitis was his admission diagnosis based on a clinical ground. We did not validate that diagnosis with any radiology test. The operation made clear that pseudoaneurysm in a proximal part of brachial artery was a correct diagnosis. Because of severe inflammation of his left upper extremity, the pseudoaneurysm was dealt with resection, ligation of the brachial artery above and below the defect and leaving the incision to heal by secondary intention. RESULTS AND CONCLUSIONS: The pseudoaneurysm was treated with excision, tying the proximal and distal ends of brachial artery without urgent revascularization, extensive debridement of all necrotic tissues and leaving the incision to heal by secondary intention. Our approach did not threaten viability of the limb, which did not show any signs of ischemia during close postoperative monitoring. Our way seems to be appropriate and in agreement with current literature. The peroperative finding stresses the necessity of standard and Doppler ultrasound in every intravenous drug abuser with clinical picture of "a typical abscess" located in groin, elbow and armpit.
Keywords: závislost na heroinu; Staphylococcal Infections; Heroin Dependence; Staphylococcus aureus; Humans; stafylokokové infekce; dospělí; Aneurysm, Infected; lidé; arteria brachialis; Substance Abuse, Intravenous; zánětlivé aneurysma; Adult; Brachial Artery; nepravé aneurysma; Male; Aneurysm, False; intravenózní abúzus drog; mužské pohlaví